Programa educativo "Games" en el mejoramiento de la expresión oral en inglés en niños del sexto grado de primaria del centro educativo particular San Francisco de Asís, Iquitos 2016 - Aspajo Nájar, Celeste (2020)
The objective of this thesis was to assess the effectiveness of a learner-training program based on the use of didactic games to improve sixth grade primary level students’ English speaking skills at San Francisco de Asis private school, Iquitos 2016. The study is evaluative in type, with research designs of: Field study, transectional contemporary, univariable, and quasi-experimental, with pre-test, post-test, and control group. The population and sample were made up by 39 students: The experimental group with 22 students (Class “A”) and the control group with 17 students (Class “B”). The data gathering tool was an achievement written test, scored with a valid and reliable rubric. Results in the post test show that the experimental group outperformed the control group as their mean score was higher (13.68 > 9.47) as well as in its indicators: Pronunciation (13,55 > 10,18), vocabulary (13,64 > 9,94), and body language (13,86 > 9,94). In conclusion, the learner-training program improved significantly the study population’s speaking skills in English and its indicators, confirming the working hypothesis as p-value was 0.000 < ? = 0.05.